Principals' and Counselors' Lens of the School Counselor's Role. Issue 1 (2nd January 2018) - Ruiz, Marybel; Peters, Michelle L.; Sawyer, Cheryl
ABSTRACT: Despite the development of structured standards and models for school counseling programs, the school counseling profession continues to struggle with role ambiguity and role conflict. To investigate this further, this study examines principals' and counselors' perceptions of the school counselor's role. A sample of 290 K–12 public school principals and counselors working in southeastern Texas school districts were solicited to complete the School Counselor Activity Rating Scale. Analysis of the findings indicates school counselors and principals only have 52% agreement regarding appropriate counselor activities as described by the SCARS. Implications for counselors and counselor educators are discussed.